Crisis Management Style in Healthcare - Nataša Podnar (Izzivi Prihodnosti, 2021)
Research question (RQ): The research aimed to find behaviour patterns of efficient crisis leaders in healthcare and, based on empiric research, develop a leadership style framework during a healthcare crisis. The study contributes to a better overview of behavioural patterns of leaders in situation of crisis. Recognition of decision-making pattern in crisis situations and use of decision model based on scientific findings can be helpful to unexperienced crisis experts, and organizations for preparation for individual crisis plan for organization. Results assist to prepare a timely response in critical situations, including choosing the most appropriate leadership approach appropriate. The study provides less experienced crisis leaders a framework of leadership pattern in healthcare crises, which is based on existing research.